Implementasi Politik Dan Etika Pendidikan Dalam Membangun Kedisiplinan Siswa di Sekolah SMP Negeri 1 Trucuk Bojonegoro - Fela Yunita Anggraini; Sri Minarti (Advances In Education Journal, 2026)
This study aims to determine the implementation of educational politics and ethics in fostering student discipline at SMP Negeri 1 Trucuk Bojonegoro. The study employed a qualitative method with a descriptive approach. Data collection included observation, interviews, and reference studies. The results indicate that the implementation of educational politics is implemented through school regulations, such as mandatory punctuality, uniform checks, restrictions on cell phone use, and providing guidance to students who violate the rules. Meanwhile, the implementation of educational ethics is evident through the culture of greetings, politeness, communal prayer, morning assembly, and congregational prayer activities, which aim to foster religious character and student discipline. The implementation of educational politics and ethics has a positive impact on student discipline, such as increased compliance with school rules and a sense of responsibility. However, obstacles remain, such as a lack of awareness among some students and inappropriate communication methods by some teachers when reprimanding students. Overall, the implementation of educational politics and ethics has created an orderly and conducive school environment and supports the development of disciplined and well-mannered students.